Nanoparticles containing β‐cyclodextrin potentially useful for the treatment of Niemann‐Pick C. Issue 3 (13th January 2020) - Donida, Bruna; Raabe, Marco; Tauffner, Bárbara; de Farias, Marcelo A.; Machado, Andryele Z.; Timm, Fernanda; Kessler, Rejane G.; Hammerschmidt, Tatiane G.; Reinhardt, Luiza S.; Brito, Verônica B.; Portugal, Rodrigo V.; Bernardi, Andressa; et al.
Abstract: β‐Cyclodextrin (β‐CD) is being considered a promising therapy for Niemann‐Pick C (NPC) disease because of its ability to mobilise the entrapped cholesterol from lysosomes, however, a major limitation is its inability to cross the blood‐brain barrier (BBB) and address the central nervous system (CNS) manifestations of the disease. Considering this, we aimed to design nanoparticles able to cross the BBB and deliver β‐CD into the CNS lysosomes. The physicochemical characteristics of β‐CD‐loaded nanoparticles were evaluated by dynamic light scattering, small‐angle X‐ray scattering, and cryogenic transmission electron microscopy. The in vitro analyses were performed with NPC dermal fibroblasts and the β‐CD‐loaded nanoparticles were tracked in vivo. The nanoparticles showed a mean diameter around 120 nm with a disordered bicontinuous inner structure. The nanoparticles did not cause decrease in cell viability, impairment in the antioxidant enzymes activity, damage to biomolecules or release of reactive species in NPC dermal fibroblasts; also, they did not induce genotoxicity or alter the mitochondrial function in healthy fibroblasts. The β‐CD‐loaded nanoparticles were taken up by lysosomes reducing the cholesterol accumulated in NPC fibroblasts and reached the CNS of mice more intensely than other organs, demonstrating advantages compared to the free β‐CD. The results demonstrated the potential of the β‐CD‐loaded nanoparticles in reducing the brain impairment of NPC.